Spillover effects of information leakages in buyer–supplier–supplier triads. Issue 3 (29th September 2020) - Ried, Leopold; Eckerd, Stephanie; Kaufmann, Lutz; Carter, Craig
Abstract: Information leakages—the unauthorized sharing of an organization's information with another organization—are a growing concern in today's supply chains, but remain relatively underexplored. Drawing on attribution theory and observational learning, our research investigates inter‐organizational information leakages from a network perspective. We assess the spillover effects of opportunistic and inadvertent information leakages between an OFFENDER organization and a VICTIM organization on the relationship between the OFFENDER and a nonpartisan OBSERVER . We consider the roles of integrity‐ and ability‐based trust, as well as operational similarity between the organizations. We conducted scenario‐based experiments with 181 sales practitioners recruited via MTurk and supplemented those results with post hoc interviews. Our results show clear spillover effects: The OBSERVER 's willingness to share information with the OFFENDER decreases significantly after any type of information leakage between the OFFENDER and the VICTIM, but more so for opportunistic leakages. Integrity‐based trust mediates the relationship between intentionality and information sharing willingness. We also find indications of an unexpected collateral damage effect in that to some extent, both trust dimensions decrease in both forms of information leakage. Further, for opportunistic information leakages, the OBSERVER 's willingness to share information with the OFFENDER decreases more when OBSERVER and VICTIM are operationally similar.